Post hoc analysis of the Exenatide‐PD trial—Factors that predict response. (6th October 2018) - Athauda, Dilan; Maclagan, Kate; Budnik, Natalia; Zampedri, Luca; Hibbert, Steve; Aviles‐Olmos, Iciar; Chowdhury, Kashfia; Skene, Simon S.; Limousin, Patricia; Foltynie, Thomas
Abstract: Exenatide, a glucagon‐like peptide‐1 agonist and a licensed treatment for Type 2 diabetes significantly reduced deterioration in motor symptoms in patients with Parkinson's disease in a randomized, placebo‐controlled trial. In addition, there were trends favouring the exenatide group in assessments of nonmotor symptoms, cognition, and quality of life. The aim of this exploratory post hoc analysis was to generate new hypotheses regarding (a) whether candidate baseline factors might predict the magnitude of response to exenatide; and (b) whether the beneficial effects of exenatide reported for the overall population are consistent in various subgroups of patients. Univariate and multivariate analyses were conducted to determine possible predictors of motor response to exenatide in this cohort. Potential treatment by subgroup interactions for changes in; motor severity, nonmotor symptoms, cognition, and quality of life after 48‐weeks treatment with exenatide were evaluated among post hoc subgroups defined by age, motor phenotype, disease duration, disease severity, body mass index (BMI), and insulin resistance. In the subgroup analyses, exenatide once‐weekly was associated with broadly improved outcome measures assessing motor severity, nonmotor symptoms, cognition, and quality of life across all subgroups, however, tremor‐dominant phenotype and lower Movement Disorder Society‐Sponsored Revision of the Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) Part‐2 scores predicted greatest motor response to exenatide and there was an indication that patients with older age of onset and disease duration over 10 years responded less well. While patients with a range of demographic and clinical factors can potentially benefit from exenatide once‐weekly, these data support an emphasis towards recruiting patients at earlier disease in future planned clinical trials of gluacagon‐like peptide‐1 (GLP‐1) receptor agonists in Parkinson's disease (PD). Abstract : While patients with a wide range of demographic and clinical factors can potentially benefit from exenatide once‐weekly, and providing the results can be replicated our data support an emphasis towards recruitment of patients at earlier stages of the disease. These exploratory findings will contribute to the design of future trials that will confirm whether such heterogeneity of the effect of exenatide exists in a larger cohort of patients.